Ω- produced in K-p reactions at 4.2 GeV/c - Hemingway, R; Armenteros, R; Dionisi, C; Gavillet, P; Gurtu, A; Holmgren, S; Losty, M; Marin, J; Mazzucato, M; Montanet, L; Banting, M; Blokzijl, R; et al. (1978)
Forty Ω- events have been observed in a large (133 events/βb) experiment at 4.2 GeV/c incident K- momentum. Thirty nine of the events come from the three-body reaction K-p→Ω-K+K0. The Ω- is mainly produced in the forward hemisphere (direction of the incident K-). The lifetime is measured to be τ = (0.75 +0.14-0.11 × 10-10 sec substantially less than the Particle Data Group value of (1.3 -0.3+0.2) × 10-10 sec. The mass is determined to be 1671.7 ± 0.6 MeV, in good agreement with other determinations. The decay asymmetry parameter α (for the decay mode Ω- → ΛK-) is found to be -0.2 ± 0.4. © 1978.